Organized Agents: Canadian Teacher Unions as Alternative Sites for Social Justice Activism - Rottmann, Cindy (Canadian Journal of Education/Revue canadienne de l’éducation, 2008)
Historically teachers’ federations have been some of the major organizational sites for social justice leadership in K-12 public education. Despite this history of activism, social justice teacher unionism remains a relatively underdeveloped concept. This article merges four philosophical conceptions of social justice in education: liberal recognition, critical recognition, liberal distribution, and critical distribution, with an analysis of equity-based initiatives articulated on the Web sites of 20 Canadian teach- ers’ organizations. The resulting framework can be used by teacher union researchers interested in generating a broader conception of social justice unionism, and teacher unionists interested in investigating their organizational practices through a social justice lens. Key words: teacher activism, teacher unionism, social justice, teacher leadership Depuis toujours, les fédérations d’enseignants font partie des principales organisa- tions qui militent pour la justice sociale dans le secteur M-12 au sein des écoles publi- ques. En dépit de cette tradition d’activisme, le syndicalisme axé sur la justice sociale chez les enseignants demeure un concept relativement peu développé. Cet article fusionne quatre conceptions philosophiques de la justice sociale en éducation – la reconnaissance libérale, la reconnaissance critique, la répartition libérale et la réparti- tion critique - avec une analyse de diverses initiatives axées sur l’équité sur les sites Web de vingt regroupements d’enseignants canadiens. Le cadre qui en résulte peut être utilisé par des chercheurs s’intéressant aux syndicats d’enseignants et voulant susciter une conception élargie du syndicalisme et de la justice sociale et par des syn- dicalistes désirant analyser leurs pratiques organisationnelles à travers la lorgnette de la justice sociale. Mots clés : activisme chez les enseignants, syndicat d’enseignants, justice sociale, leadership des enseignants